CFD Sehat: Skrining tekanan darah, gula darah, dan edukasi PTM di Selong - Faradila Faradila; Arief Rahman; Andi Nizam Harahap; Ero Ari Angga; Intan Nefia Alamanda; Lalu Ramadlan; Raania Amaani; Hartini Haritani (Universitas Hamzanwadi, 2025)
Car Free Day (CFD) events offer a practical venue for health promotion and early detection of noncommunicable diseases (NCDs). This community service program aimed to conduct blood pressure and random blood glucose screening while delivering brief NCD prevention education to the public at CFD Taman Rinjani, Selong. The activity was implemented on 30 November 2025 and involved 80 participants. The program included on-site measurements of blood pressure and random blood glucose, descriptive grouping of results by age and sex, and short counseling on NCD prevention and recommended follow-up. The findings indicated an age-related increase in mean systolic blood pressure, with the highest proportion of hypertension observed among older adults. Across younger and mid-adult groups, hypertension tended to be more frequent in men than in women. Elevated random blood glucose was uncommon overall but appeared mainly among women and was more noticeable in the older-age group. In summary, integrating screening and education in a public setting can help identify at-risk groups and encourage regular check-ups. Regularly scheduled CFD-based programs supported by selective referral pathways and strengthened lifestyle education may contribute to NCD risk reduction.